New angiospermic taxa for the flora of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2017)
This paper presents addition of 89 taxa under 64 genera distributed in 32 families for the flora of Bangladesh which are not included in the monumental works Flora of British India, Bengal Plants and Encyclopedia of Flora and Fauna of Bangladesh. Updated nomenclature, family name, references to the work and the precise localities have been furnished under each taxon.Bangladesh J. Plant Taxon. 24(2): 165–171.